Transcending the national: on worlding the peripheral literatures. - Pokrivčák, Anton; Zelenka, Miloš (Neohelicon, 2023)
The study is concerned with contemporary theoretical concepts of world literature ("literature of the world", "worldliness of literature", "world literary system", "world literary republic"). Considering the results of the XXII International Congress ICLA/AICL in Macau 2019, it discusses how the concepts are reflected in the Slovenian scholar Marko Juvan´s monograph Worlding a Peripheral Literature (2019). The book analyses conditions under which small national texts (for example, Slavic) become world texts. According to Juvan, the space of world literature was historically originating in the mid-nineteenth century, in parallel with the genesis of national literatures. The decisive factors of this process included the importance of language and the significance of the country. On the one hand, Juvan's idea of world literature admits that an acceptable consensus can be reached in the form of an epistemological and terminological basis defined by a set of concrete concepts and principles, on the other hand, the acceptance of inequality between the so-called big and small literatures as a way of thinking is a consequence of economic and mass media globalization. Overall, however, Juvan's concept, inspired by Moretti's theory of evolution and economic models, brings a fundamental theoretical contribution to current discussions on the forms, essence, and functions of world literature as a universal phenomenon.